Analisis Kelayakan Internal Dan Eksternal Pembangunan Rumah Potong Ayam Yang Terintegrasi Dengan Proses Pendingin Di Kabupaten Minahasa Utara - Wenas, Mercy Sisilya; Rengkung, Leonardus Ricky; Jocom, Sherly Gladys (Sam Ratulangi University, 2023)
This study aims to analyze the internal and external feasibility of building a chicken slaughterhouse (CS) integrated with the freezing process. This research was conducted in North Minahasa Regency. This research was carried out from January to September 2022 starting from the process of preparing proposals, data collection, analysis to presenting data in the results of research reports. The method used to analyze internal factors is the CANVAS method and the PESTEL method is used to analyze external factors. Techniques and data collection were carried out through interviews with 15 (fifteen) informants, observation, documentation and literature studies. This study uses primary data obtained directly from relevant informants to obtain profile data on breeders, data on frozen chickens imported from outside the region, and technical and environmental related matters. While secondary data was collected from various sources including BPS data, previous research journals and the latest information from the internet related to RPA and frozen chicken. The results of the research based on financial calculations show that the CS business is very profitable in terms of business and investment where the CS which is integrated with the cooling process is feasible to build in North Minahasa Regency.